The Influence of Dress Style on Catcalling in Female Students - Bagus Wahyu Alamsya; Manah Rasmanah; Hartika Utami Fitri (al-Afkar, Journal For Islamic Studies, 2025)
This study is entitled "The Influence of Dressing Style on Catcalling Treatment in Female Students" the researcher has the following objectives: to find out how the description of the level of dress style of female students of Raden Fatah State Islamic University Palembang, to find out how the description of the level of catcalling treatment in female students of Raden Fatah State Islamic University Palembang, and to find out how the influence of dress style on catcalling treatment in female students. This study is a quantitative approach that is correlational. The sample in this study amounted to 93 female students who have been drawn using the Solvin formula and the value of e = 0.1 (10%) from a population of 1216 female students. The data collection technique used a questionnaire distributed to 93 female students and documentation. The instrument test is a validity and reliability test. The data analysis technique is simple linear regression. The results of the study showed that 65 female students (70%) were in the moderate level of dress, then 60 female students (65%) experienced catcalling treatment in the moderate level and the results of the influence of the way of dressing on the treatment of catcalling on female students had a significant negative effect, this can be seen from the t count of -7.268> -1.986 t table with a significance of 0.000 <0.05. So there is an influence of the way of dressing on the treatment of catcalling partially accepted. This means that the more sharia the way of dressing of female students, the more they will avoid catcalling.